A web based tool for HCI-Orientated massive asynchronous linear card sorting - Mohamedally, Dean; Zaphiris, Panayiotis; Petrie, Helen (My University, 2003)
This paper presents an initial iterative design and implementation of a web based linear card sorting tool. Card sorting is a participant based knowledge elicitation technique for grouping information into categorical domains. We have constructed a tool that HCI specialists and others can utilise to gather data from demographic groups. This would allow large numbers of participants to take part in card sorting experiments asynchronously (in their own time) via using a web browser. The advantages of using this tool as part of a card sorting technique are firstly the possibility of aggregation of data from particular demographical arenas on a wide scale and secondly the fact that the output data is in a format that is easily parsable by a cluster analysis tool. To better evaluate its design and implementation a pilot test was conducted with HCI specialists as the target group.
Keywords: Card sorting; Prototyping; Design; Java